(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
Innovation involves its study in various scientific areas for social and business improvement. However, when it comes to innovation in craftsmanship, questions arise about its functioning and how it integrates into the market. Craftsmanship, as a product and characteristic symbol of the place, requires its creators, aged between 20 and 40, to seek ways to integrate it into the market. In this mixed, cross-sectional, and non-experimental research, textile artisans from Cuetzalan del Progreso, in the state of Puebla, considered innovation as a unique characteristic of a tourist context. Through socio-economic indicators, artisans recognize a lack of application of innovation processes, making production processes inefficient. One piece of evidence is marketing as an indicator of innovation, which identifies features that seek new spaces to maintain relevance in the market.